Mental health and well-being during COVID-19 lockdown: A survey case report of high-level male and female players of an Italian Serie A football club - Ivarsson, A.; McCall, A.; Mutch, S.; Giuliani, A.; Bassetto, R.; Fanchini, M. (Science and Medicine in Football, 2021)
Objectives: The objective of the study was to describe high-level senior and junior, male and female footballers` levels and changes in mental health and well-being throughout a 8-week period of varying lockdown conditions and restricted training during the first wave of the COVID-19 pandemic. Method: One-hundred and one player`s belonging to four teams (female first team, U19 female, male first team and U19 male team) of the same Italian Serie A club were involved in the study. Data were collected through an online questionnaire, and administered at 2, 3, 5, 7 and 9 weeks after the start of the lockdown period in Italy. Well-being as well as positive and negative affects measurements were examined. Results: Across the five measures, 36% of players reported clinical levels in depressive symptoms (scores = 50) on at least one occasion. Thirteen percent of the players reported clinical levels on more than 50% of the measurement occasions. There was a credible decrease in depressive symptoms as well as negative affects over the five measurement points. No credible change was found in positive affects. Conclusions: The results showed that prevalence of players reporting clinical levels of depressive symptoms was higher than has been shown previously in high-level athletes. The prevalence did, however, decrease during the 8-week period. A similar trend was found for negative affects, but no linear trend for positive affects. Overall, despite a higher prevalence in depressive symptoms earlier during lockdown, this improved as players progressed towards fewer restrictions and normal training situation.